Theorizing Energy Geographies. Issue 6 (June 2015) - Huber, Matthew
Abstract Geography is witnessing a "boom" in energy research that has emerged alongside renewed interest in the humanities and social sciences over the role of energy in shaping modern social life. In this review article, I suggest that geographers need to connect better with new debates in critical social theory over energy through an emphasis on energy's role in the social production of space. I first review recent interventions in the social sciences and humanities on energy and suggest that as insightful as they are, they lack an attention to geography. It reviews how energy used to be a central theoretical concept in geography – specifically through "cultural ecological" approaches that saw the flow of energy and nutrients through human groups as a central aspect in explaining their cultural traits. The rise of political ecology – and its focus on resources rather than energy – led to energy becoming seen as simply an empirical object on inquiry as opposed to an underlying concept. Second, I argue political ecologies of energy are central to the production and reproduction of geopolitical imaginaries of nationhood and international relations, and thus, energy should be at the center of theorizing these ideas. Third, although geographers have long viewed urbanization as a sociospatial – and increasingly socioecological – process, the role of energy in shaping the material infrastructure and uneven nature of cities has been less discussed. Fourth, the ways in which energy is consumed, and the way energy shapes the geographies of everyday practice, is a critical aspect in the production of space. Fifth, I suggest that any energy transition toward a low‐carbon energy system must understand that new energy systems will also require new spatialities and new spatial imaginations.